Um estudo discursivo dos blogs: sentidos de/sobre homofobia - Bastos, Gustavo Grandini (2013)
The present work aims to investigate how the homosexuals talk about homophobia through blogs (online diaries) having as analytical, methodological and theoretical reference the French Discourse Analysis. The new information and communication technologies have been providing new discursive spaces like blogs that have specific writing productions. The research made it possible to observe the dislocations and repetitions used by gay subjects (the ones who write / post and the ones who read the blogs) that affect the circulations and production of discourses and meanings about homophobia. In those discourses we can notice the productions of different meanings about the prejudice present in those blogs. The corpus of this research is composed by 37 excerpts, comments and posts from three blogs that use the online- diary format, written by brazilian homosexuals. The results obtained by analyzing them allowed the identification of the blogs as information spaces where there are reports of violence (occurred in different moments of their lives) narrated by the subjects. It is also possible to identify marks that highlight homophobia as part of their everyday lives affecting them and the way they themselves use homophobic expressions. By using the discourse that is available, the subjects write their texts sharing reports and building together that discursive space